Pengaruh Rasio Karet Alam Terdeproteinisasi dengan Monomer Vinil terhadap Karakteristik Karet Alam Termoplastik - Santi Puspitasari; Emil Budianto; Dadi Rusadi Maspanger (Pusat Penelitian dan Pengembangan Perkebunan, 2016)
Chemical modification of natural rubber latex by emulsion graft copolymerization with thermoplastic monomer produces thermoplastic natural rubber (TPNR). Ratio composition of natural rubber to thermoplastic monomer determines the TPNR properties. TPNR has good mechanical properties of natural rubber and high processability of plastic material thus enhancing its application in industry. The research, which was conducted at research laboratory of Indonesian Rubber Research Institute, from June to December 2014, aimed to study the effect of the ratio of deproteinized natural rubber (DPNR) latex to vinyl monomer (VM: methyl methacrylate and styrene) on physical and mechanical properties of TPNR produced from batch graft copolymerization. Batch graft copolymerization was conducted at certain ratios of DPNR latex with methyl methacrylate and styrene (70:30; 60:40; and 50:50) at (65°C, 5 hours), and subsequently at (70°C, 1 hour). The result showed that batch technique tend to cause the formation of homopolymer vinyl which also affected the TPNR properties. Visually, the TPNR had white color, hard and brittle texture yet easier to process as shown by low time and energy consumption during compounding. The ratio of DPNR to VM at 70:30 was regarded as the optimum ratio for its balanced properties between elastomeric material of DPNR and thermoplastic material of VM.